PANDANGAN IBNU TAIMIYAH TENTANG PERAN NEGARA DALAM MENSTABILKAN EKONOMI - Anggun Khairunnissa Agustin; Cici El Dirrah Syafitri S; Haura Afnani Zanjabila; Syahla Nabila; Fitri Hayati (JSE: Jurnal Sharia Economica, 2025)
This paper examines Ibn Taymiyyah’s views on the role of the state in stabilizing the economy. Ibn Taymiyyah, although advocating free market mechanisms, acknowledged the need for state intervention in certain conditions, such as the presence of injustice (monopoly, fraud), or emergencies. This intervention focused on market supervision and regulation, not forced pricing. The state also played an important role in preventing hoarding (ihtikar), ensuring the availability and distribution of goods through supervisory institutions such as hisbah, and upholding economic justice by encouraging zakat, sadaqah, and prohibiting usury. Ibn Taymiyyah’s thoughts are relevant to the modern economic context, especially in the context of contemporary Islamic economics, providing a basis for fiscal policy, price control, and the application of the hisbah principle in the digital era.